Cutting to the Chase: Donor Expediency Drives the Campaign for Safe Male Circumcision in Botswana. Issue 2 (4th March 2017) - Johnson, Krista
Abstract : Safe male circumcision (SMC) is being heralded in the scientific and policy communities as a highly effective intervention that could significantly reduce the number of people being infected with HIV in a number of high-prevalence countries in southern Africa. However, the scale-up of SMC in most southern African countries has been slow. This article uses the case of male circumcision in Botswana to examine the political factors that have contributed to the slow uptake, with particular emphasis on donor–recipient relations. I argue that evidence-based policy-making in the case of the male circumcision campaign is in conflict with Botswana's tradition of deliberative policy making, contributing to the slow uptake of the programme. I also highlight some of the pitfalls for evidence-based interventions that do not sufficiently take into consideration the social, cultural and political context. Basic and clinical science have provided us with highly effective interventions to treat and prevent HIV infection. If we markedly scale-up globally the implementation of these interventions, we can dramatically alter the trajectory of the pandemic towards the ultimate goal of an AIDS-free generation.